CT Imaging of Primary Pulmonary Lymphoma. (15th August 2018) - Lynch, Peter; Landis, Mark
Abstract : Primary pulmonary lymphoma is a relatively uncommon disease in both the thoracic and lymphoproliferative spectrum of cancers, accounting for only up to 1% of primary pulmonary malignancies and fewer than 1% of all lymphomas.1 Diagnosis requires pathologic confirmation of the lymphoproliferative disorder in the lungs, with no detectable extrathoracic manifestations of the disease for at least 3 months after the initial diagnosis to avoid accidental inclusion of lymphoma that has secondarily progressed to involve the lungs.